2012
DOI: 10.1517/17530059.2012.694423
|View full text |Cite
|
Sign up to set email alerts
|

The role of anti-cyclic citrullinated peptide (CCP) antibodies in early detection of rheumatoid arthritis: an overview of the INOVA Diagnostics, Inc. QUANTA Lite CCP assays

Abstract: Detection of anti-CCP antibodies has emerged as one of the most important disease markers in RA patients. Several methods are available to measure anti-CCP antibodies, and isotyping and identification of citrullination targets are now the next step in further characterizing these autoantibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A meta-analysis [46] has shown that the pooled sensitivities of ACPA and RF are similar, but ACPA positivity is more specific for RA than IgM RF, IgG RF, or IgA RF positivity [61] and more specific for early RA than IgM RF [62]. On the other hand, sensitivity is reduced because positivity for both ACPA and RF is a more stringent criterion than positivity for either alone [46]; combining ACPA and RF positivity is more permissive in terms of sensitivity because the antibodies complement each other, especially for early RA [6366]. …”
Section: Rfs and Rheumatoid Arthritismentioning
confidence: 99%
“…A meta-analysis [46] has shown that the pooled sensitivities of ACPA and RF are similar, but ACPA positivity is more specific for RA than IgM RF, IgG RF, or IgA RF positivity [61] and more specific for early RA than IgM RF [62]. On the other hand, sensitivity is reduced because positivity for both ACPA and RF is a more stringent criterion than positivity for either alone [46]; combining ACPA and RF positivity is more permissive in terms of sensitivity because the antibodies complement each other, especially for early RA [6366]. …”
Section: Rfs and Rheumatoid Arthritismentioning
confidence: 99%
“…As generally accepted, RF and anti-CCP antibodies are important markers for the diagnosis and prognosis of RA ( 53 ). Numerous clinical data have shown that RF is not specific for RA diagnosis, and approximately 30% to 45% of patients with RA do not have RF ( 54 ). Anti-CCP antibody is an index of the prognosis of RA and is extremely specific for RA diagnosis ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both RF and anti-CCP2 have similar sensitivities for the diagnosis of RA but anti-CCP2 is more specific [ 14 ]. Anti-CCP2 is positive in 20%-30% of RA patients who are negative for RF [ 15 ]. A systemic review and meta-analysis that included 37 studies of anti-CCP2 positive patients and 50 studies of RF positive patients showed the pooled sensitivities of RF and anti-CCP2 to be 69% and 67%, and 85% and 95%, respectively [ 16 ].…”
Section: Reviewmentioning
confidence: 99%